Dumb money [videorecording (Blu-Ray)] - Blum, Lauren Schuker; Angelo, Rebecca; Dano, Paul, 1984-; Davidson, Pete, 1993-; D'Onofrio, Vincent; Ferrera, America, 1984-; Herrold, Myha'la, 1996-; Offerman, Nick, 1970-; Ramos, Anthony; Ryder, Talia; Stan, Sebastian, 1982-; Woodley, Shailene; et al. (Sony Pictures Home Entertainment, 2023)
Dumb Money is the ultimate David vs. Goliath tale, based on the insane true story of everyday people who flipped the script on Wall Street and got rich by turning GameStop (yes, the mall videogame store) into the world's hottest company. In the middle of everything is regular guy Keith Gill, who starts it all by sinking his life savings into the stock and posting about it. When his social posts start blowing up, so does his life and the lives of everyone following him. As a stock tip becomes a movement, everyone gets rich until the billionaires fight back, and both sides find their worlds turned upside down.